Adoption Index of Women Goat Farmers in Various Aspirational District of Niti-Ayog in West Bengal, India - Santra, Bikash; Goswami, A.; Dhara, K. C.; Biswas, Sukanta (International Journal of Bio-resource and Stress Management, 2021)
The Goat husbandry plays a key role in sustainable livelihood and income generation of the rural small-marginal farmers, landless laborers and specially women folk. The research work was carried out on adoption index of women goat farmers in purposively selected 05 nos. of aspiration districts, of NITI Aayog, GOI in W.B. From each one block of each district50 nos. of women goat farmers’ were randomly selected as respondents with total sample size of 250 nos. for the present study. The collected data were compiled and analyzed statistically with the help of pre-tested structured interview schedule for better interpretation of the findings of the study. The study had showed low level of adoption among the farm women, which indicated their lacking in application of improved husbandry practices in goat farming. The study revealed that, majority of farm women of Birbhum district were having higher % age of low adoption level in comparison to other four districts. The findings also revealed that, joint family married women were having more adoption index than nuclear family. The study explored that, South Dinajpur district had highest adoption level in terms of almost all enlisted adoption indicators than other four aspirational districts in the study. In future, a comprehensive farmer training and demonstration programme need to be conducted in this area for livelihood improvement of women goat farmers. The adoption level about goat farming need to be assessed for formulation of sustainable livelihood based promising endeavor in this functional area of the state of W.B.